Teledentistry sebagai Penunjang Kesehatan Rongga Mulut Selama Masa Pandemi Covid-19 - Desy Purnama Sari (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2021)
The covid-19 pandemic causes the crippling effect on the oral healthcare. Dental practitioners has a very high risk contamination and transmission of covid-19, thus teledentistry is recommended to be an innovative solution to overcome these problems. The purpose of writing is to explore the usefulness of teledentistry services during the covid-19 pandemic. Relevant articles were selected based on the title and abstract used Google Search and Pubmed and published in 2020, then categorized into: 1) related to teledentistry and covid-19, (2) available in full text in English, (3) the use of teledentistry during the covid-19 pandemic. 89 articles appropriate to the initial search criteria. After deletion of duplicate articles, only 52 articles remained and were reviewed by title and abstract, resulting in 27 full-text articles. Seven of the full text articles met the inclusion criteria regarding the use of teledentistry during the COVID-19 pandemic. Teledentistry is very effective and efficient innovation that can reduce direct contact and prevent the spread of covid-19. In this new normal era is highly recommended to improve the software application and manage the teledentistry system with the best standard, to support the teledentistry as the vital factor in delivering dental services.